2012
DOI: 10.1100/2012/485193
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Catechin in Northeast Indian Tea Cultivars

Abstract: Tea (Camellia sinensis L.) leaf contains a large amount of catechins (a group of very active flavonoids) which contribute to major quality attributes of black tea. Based on morphological characters tea plants were classified as Assam, China, and Cambod varieties. The present study is an attempt for biochemical fingerprinting of the tea varieties based on catechin composition in green leaf of cultivars grown in Northeast India. Assam variety cultivars contained the highest level of catechins followed by Cambod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 23 publications
1
28
0
3
Order By: Relevance
“…Catechins are water soluble flavanols that constitute ;25% of the dry weight of green tea, and epigallocatechin gallate (EGCG) accounts for approximately half of the tea catechins (Sabhapondit et al, 2012). Previous work on the interactions of SULTs and dietary chemicals revealed that EGCG is a potent inhibitor of SULT1A1 (K i = 42 nM).…”
Section: Resultsmentioning
confidence: 99%
“…Catechins are water soluble flavanols that constitute ;25% of the dry weight of green tea, and epigallocatechin gallate (EGCG) accounts for approximately half of the tea catechins (Sabhapondit et al, 2012). Previous work on the interactions of SULTs and dietary chemicals revealed that EGCG is a potent inhibitor of SULT1A1 (K i = 42 nM).…”
Section: Resultsmentioning
confidence: 99%
“…The variations of EGCG and EGC were the most prominent among the different tea varieties. High EGC content was found to be a characteristic of the Assam variety which was further corroborated through multivariate analysis (Sabhapondit et al 2012). Although accuracy was higher than morphological markers, accumulations of chemicals were subjected to post-transcriptional modification which often restricted their utility as markers (Staub et al 1982).…”
Section: Biochemical Markersmentioning
confidence: 93%
“…However, no attempts have been made in systematic characterization of tea germplasm using biochemical parameters of Sri Lankan tea genetic resources. On the contrary, some other tea producing countries such as China, Japan, India and Kenya have used biochemical constituents like total catechins and their fractions, total polyphenols, chlorophylls, carotenoids and caffeine in the fresh leaf as discriminative markers for characterizing their tea germplasms to evaluate diversity and genetic potential warehoused in the germplasm (Magoma et al, 2003;Chen & Zhou, 2005;Lopez et al, 2005;Saravanan et al, 2005;Gulati et al, 2009;Sabhapondit et al, 2012).…”
Section: December 2013mentioning
confidence: 99%